Patient rights in Malaysia - What's new on this bumpy ride? - Talib, N. (2007)
It is no surprise that generally in a doctor-patient relationship, the dynamics has always been that the doctor retains the upper hand and the patient at the same time willingly allows for this or even that he wants it to be that way. Perhaps this might be explained by the fact that the patient, when presenting himself at the doctor's surgery, is hoping and therefore trusting the doctor's professional judgment so as to be able to identify and diagnose what is ailing him, and then accordingly treat him so that his health is restored. This trust is what underlies the doctor-patient relationship.